Парламент Финляндии - Аувинен Оллиюхани (Парламент Финляндии, 1990)
Экземпляры: КР (20100301) / Инвентарный номер: 1015106 / Цена: 1000.00 / Сис.шифр: 67.400 / Авт.знак: П 18 / ГРНТИ: 10 / ББК: 67.400.621(4Фин)